DYNAMICS CHARACTERISTICS AND EXPERIMENTAL ANALYSIS ON THE OBLIQUE CUTTING OF PLOW SYSTEM - ZHANG Yu; CHEN HongYue; HAO ZhiYong; MAO Jun (Jixie qiangdu)
Aiming at the mechanical properties of plow head and dynamic charateristics of system under oblique cutting condition,cutting resistance of planning tool under oblique cutting condition was derived,and was treated as external excitation. Dynamic differential equation of plow system were established by using the finite element method,and were solved by using numerical method. The effect of oblique cutting velocity、cutting depth、cutting location、middle trough angle offset on dynamic charateristics of plow system. The dynamic charateristics of plow system were tested based on the mechanical test experimental platform. The test results and theoretical results were compared. The research results provided theoretical basis for working stability、fatigue life of key parts、process parameters optimization of plow system.